Role of interleukin-21 and interleukin-21 receptor polymorphisms in the treatment of HBeAg-positive chronic hepatitis B patients with peginterferon. Issue 23 (June 2018) - Wang, Xia; Xu, Zhi-Qiang; Fu, Juan-Juan; Cheng, Li-Wei; Li, Yan; Li, Li; Pan, Xiu-Cheng
Abstract : Abstract: The aim of this study was to evaluate the relationship between interleukin-21 (IL-21) and interleukin-21 receptor (IL-21R) polymorphisms and the response to peginterferon alfa (PEG-IFN α) therapy in HBeAg-positive chronic hepatitis B (CHB) patients. A total of 143 HBeAg-positive CHB patients treated for 48 weeks with PEG-IFN α and followed up for 24 weeks post-treatment were retrospectively evaluated. Genotypes analysis was performed for IL-21 polymorphisms rs907715, rs2221903, and IL-21R polymorphisms rs3093301 and rs2285452. Serum IL-21 levels were measured by enzyme-linked immunosorbent assay. The end of virological response (EVR) rate was 46.9% (67/143) at the end of treatment, the sustained virological response (SVR) rate was 43.4% (62/143) and the complete response (CR) rate was 32.1% (46/143) at 24 weeks post-treatment. Patients who carried IL-21 rs 2221903 genotype AA had a rather higher rate of EVR (response rate: 52.4%, odds ratio [OR] 0.42, 95% confidence interval [CI]: 0.19–0.91, P  = .021), SVR (response rate: 47.6%, OR 0.43, 95% CI: 0.19–0.95, P  = .028), and CR( response rate: 38.1%, OR 0.31, 95% CI: 0.12–0.79, P  = .014) when compared to those had AG genotype. Meanwhile, IL-21rs 2221903 genotype AA was also independently associated with markedly reduced HBsAg levels (>1og10  IU/mL) after 24 weeks treatment and low HBsAg levels (<100 IU/mL) at the end of treatment. IL-21 rs907715 AG/GG genotype was independently associated with SVR (OR: 2.92, 95% CI: 0.98–8.6, P  = .039; OR: 3.23, 95% CI: 1.0–10.4, P  = .039). Patients with IL-21 rs907715 AG/GG genotype had higher serum IL-21 levels than those with rs907715 AA genotype ( P  = .021). IL-21 rs2221903 and rs907715 polymorphisms were significantly associated with the treatment response to PEG-IFN α among Chinese HBeAg-positive CHB patients. Abstract : Supplemental Digital Content is available in the text